2019
DOI: 10.1001/jamainternmed.2018.8766
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day vs Different-Day Elective Upper and Lower Endoscopic Procedures by Setting

Abstract: Performing elective upper and lower endoscopic procedures on the same day is a patient-centered and less costly approach than a 2-stage approach performed on different days, when clinically appropriate. Whether this practice pattern varies based on practice setting has not been studied. OBJECTIVES To estimate the rate of different-day upper and lower endoscopic procedures in 3 types of outpatient settings and investigate the factors associated with the performance of these procedures on different days. DESIGN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…37 In this context of absent or conflicting recommendations, most respondents in the present survey study nonetheless reported they would obtain screening CBCs for patients who were pregnant or not pregnant. Prior work 38,39 has also reported underuse of bidirectional endoscopy, although not to the extent found in our study. Although previous guidelines recommended bidirectional endoscopy for men and postmenopausal women, 11 subsequent American Gastroenterological Association guidelines, published after this survey was conducted, recommend bidirectional endoscopy regardless of menopausal status for those without an alternate explanation for IDA.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…37 In this context of absent or conflicting recommendations, most respondents in the present survey study nonetheless reported they would obtain screening CBCs for patients who were pregnant or not pregnant. Prior work 38,39 has also reported underuse of bidirectional endoscopy, although not to the extent found in our study. Although previous guidelines recommended bidirectional endoscopy for men and postmenopausal women, 11 subsequent American Gastroenterological Association guidelines, published after this survey was conducted, recommend bidirectional endoscopy regardless of menopausal status for those without an alternate explanation for IDA.…”
Section: Discussioncontrasting
confidence: 49%
“…For example, in some practice settings, insurance reimbursements may disincentivize combined EGD and colonoscopy, and physicians may not offer the combined procedures in a single appointment. 38,39 However, a serial diagnostic testing approach may lead to increased costs and require that patients undergo a second episode of sedation. In addition, if there is a substantial time interval between the colonoscopy and the EGD, there is the theoretical potential for a delay in diagnosis (although serial testing was not directly assessed in this survey study).…”
Section: Discussionmentioning
confidence: 99%
“…In this edition of JAMA Internal Medicine, Wang et al 5 highlight a third and novel approach to understanding how we could improve the value of care, focusing on medical procedures (Table ). Rather than focusing on frequency (how often the procedure occurs) or price (how much was paid for each procedure), they assessed the timing of concurrent procedures.…”
Section: Invited Commentarymentioning
confidence: 99%
“…In some clinical scenarios (eg, iron deficiency anemia, where there is a higher risk of gastrointestinal malignant neoplasms), it is inappropriate to not perform both procedures on the same day. In this context, Wang et al 5 found wide variation in how often upper and lower endoscopic procedures were performed together (on the same day) vs on different days. Specifically, they reported a greater than 3-fold variation in different-day procedure rates when stratified by practice environment (47.7 % in physician offices vs 22.2% in ambulatory surgery centers vs 13.6% in hospital outpatient departments).…”
Section: Invited Commentarymentioning
confidence: 99%
See 1 more Smart Citation